Consensus Tracking Control of Multiple Quadrotors with a Cooperative Leader - Noor Hanis Izzuddin Mat Lazim; Liyana Ramli; Abdul Rashid Husain; Nurul Adilla Mohd Subha; Mohd Ariffanan Mohd Basri (ARQII Publication, 2024)
Non-Indexed Publication